Divine Milestones : A Global Vision Beyond the American Dream - Sohn, David (Xlibris, 2016)
Book's contents: the story of author Dr. David Sohn's professional life and how, as a Korean, was able to achieve the American Dream, but on a bigger, global scale. Divine Milestones is an inspiring book where author David Sohn uses his intellect and talents to better the world. God presents milestones in our lifetime to achieve His plan for us, but God allows us to exercise free will to take routes different from His optimal route. God created us with a special purpose were may not know. His plan for one person might be uniquely different from His plans given to other people.